Yellow Biotechnology I Insect Biotechnologie in Drug Discovery and Preclinical Research - Vilcinskas, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Yan Wang, De-Dong Li, Yuan-Ying Jiang and Eleftherios Mylonakis Utility of Insects for Studying Human Pathogens and Evaluating New Antimicrobial Agents Krishnendu Mukherjee, Ramya Raju, Rainer Fischer and Andreas Vilcinskas Galleria Mellonella as a Model Host to Study Gut Microbe Homeostasis and Brain Infection by the Human Pathogen Listeria Monocytogenes DisordersJulia Hoffmann, Renja Romey, Christine Fink and Thomas Roeder Drosophila as a Model to Study Metabolic Annely Brandt and Andreas Vilcinskas The Fruit Fly Drosophila melanogaster as a Model for Aging Research Theodoulakis Christofi and Yiorgos Apidianakis Drosophila and the Hallmarks of Cancer Stefanie Grünwald, Iris V. Adam, Ana-Maria Gurmai, Ludmila Bauer, Michael Boll, and Uwe Wenzel The red flour beetle Tribolium castaneum as a model to monitor food safety and functionality Alexander O. Brachmann and Helge B. Bode Identification and Bioanalysis of Natural Products from Insect Symbionts and Pathogens Jette Pretzel, Franziska Mohring, Stefan Rahlfs and Katja Becker Antiparasitic Peptides
Utility of Insects for Studying Human Pathogens and Evaluating New Antimicrobial Agents -- Galleria Mellonella as a Model Host to Study Gut Microbe Homeostasis and Brain Infection by the Human Pathogen Listeria Monocytogenes -- Drosophila as a Model to Study Metabolic Disorders -- The Fruit Fly Drosophila melanogaster as a Model for Aging Research -- Drosophila and the Hallmarks of Cancer -- The red flour beetle Tribolium castaneum as a model to monitor food safety and functionality -- Identification and Bioanalysis of Natural Products from Insect Symbionts and Pathogens -- Antiparasitic Peptides.
Keywords: Chemistry; Biotechnology; Applied Ecology; Biomedical engineering; Chemistry; Biotechnology; Applied Ecology; Biomedical Engineering